Mô hình hệ thống làm việc hiệu suất cao và ứng dụng trong ngành ngân hàng ở Thành phố Hồ Chí Minh - Bùi Thị Phương, Linh; Trần Kim , Dung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This study examined the relationship between the high-performance work systems (HPWS)- serviceability- business performance chain in the banking sector in Ho Chi Minh City. Using data collected from 386 bank branches and transaction offices of 17 banks and employing the PLS analytical technique, we found that HPWS has a positive impact on business performance, which is mediated by serviceability. The findings provide a solid foundation for bank managers to make informed decisions regarding investments in HPWS and enhancing service capability to optimize business performance.